Factors affecting social adaptability of Three Gorges Reservoir Area migrants - Wang Shunke (2016)
In this thesis, migrant households around eight districts and counties in the Three Gorges Reservoir Area (TGRA) and nine resettlement provinces & municipalities have been surveyed, and 983 migrant households have been sampled, on the basis of which we have built up models for multivariate regression analysis to explore the social adaptability of migrants and the roles of some factors affecting it. Research findings show that the social adaptability of migrants has something to do with the general migration policies, as well as specific factors such as their mindsets, residential conditions, social relations, family income, production environment and the like. Among these factors, the migration policies and their interactive factors play a significant role. If the differences in resettlement regions, migrant education, age and professionalism are observable, their role will be quite significant. Thus, a series of policy recommendations on planning and migration policies have been made, to identify resettlements based on the dual-principle, and to carry out vocational skills promotion programs.